Maintenance of metaphase chromosome architecture by condensin I - Piskadto, Ewa (2020)
"Faithful segregation of the genome into two daughter cells is one of the most fundamental events for every living organism. In each round of the cell cycle, cells need to orchestrate a sequence of complex steps to replicate their genetic material, pack it neatly into mitotic chromosomes and perform their precise separation when all the prerequisites are met. One of the most fascinating questions in biology is to understand the internal organization of mitotic chromosomes. Even though mitotic chromosomes were first described around 140 years ago, how exactly interphase DNA molecules are packed to become mitotic chromosomes is still a mystery. Despite the lack of precise details about chromosome condensation mechanisms, it is believed that in the heart of this process lies a group of protein complexes called condensins. The mechanism by which condensins are able to enforce or guide the condensation process is yet unknown. In this thesis, we will present our advances in understanding condensin’s function in maintaining mitotic chromosome compaction and internal architecture.(...)"